The BRIDGE project: a feasibility randomised controlled trial of brief, intensive assessment and integrated formulation for young people (age 14-24) with features of borderline personality disorder (Protocol) - Gajwani, Ruchika; Sim, Fiona; McAllister, Kirsty; Smith, Helen; McIntosh, Emma; Moran, Paul; Ougrin, Dennis; Smith, Michael; Gumley, Andrew Ian; Chanen, Andrew M.; Minnis, Helen (Frontiers in Psychiatry, 2024)
Background Borderline personality disorder (BPD) is a severe mental disorder that is characterised by a pervasive pattern of instability of interpersonal relationships, self-image, and mood as well as marked impulsivity. BPD has its peak incidence and prevalence from puberty through to emerging adulthood. BPD is a controversial diagnosis in young people. Commonly, young people with BPD are under-diagnosed, untreated, are not in employment or training and are estranged from their families. Yet, they have complex needs and are at high suicide risk. Aim To assess the feasibility of conducting a randomised controlled trial (f-RCT) of a BRIDGE, a brief intervention programme for young people (age 14-24) with BPD symptoms (sub-threshold or threshold) in a community sample from Scotland, UK. Method Forty young people (age 14-24) meeting criteria for BPD symptoms, will be randomised in a 1:1 ratio to receive either a) the BRIDGE intervention plus service-as-usual or b) service-as-usual alone. Follow up will be 12 weeks and 24 weeks post-intervention. The study is carried out between 2021 to 2024. Outcome The two primary outcomes of the MQ funded, BRIDGE project (f-RCT) are i. recruitment rates and ii. retention rates. The study will present the acceptability and appropriateness of our putative outcome measures for a future definitive randomised controlled trial (d-RCT). Impact Young people with BPD benefit from good clinical care and targeted intervention, however are regularly missed or mislabelled. The community based feasibility trial would provide initial evidence of variable needs of young people with complex needs, who maybe missed or excluded from services as they don’t “fit” a model/diagnosis. Workable multi-agency service model proposed in the trial would be a major advance in understanding care pathways regardless of trial outcome. Clinical Trial Registration ClinicalTrial.gov, identifier NCT05023447